النمط الجسمي للرياضيين الناشئين بعمر 12-15 سنة - معلم, عبدالمالك (جامعة الوادي - University of Eloued, 2023)
ملخص: هدفت الدراسة الى التعرف على النمط الجسمي للرياضيين الناشئين من خلال مقارنتهم بأقرانهم غير الرياضيين، شملت الدراسة عينة قوامها (188) ناشئ تتراوح أعمارهم بين (12و15) سنة، تم توزيعهم على مجموعتين، الأولى تتشكل من (94) رياضي والثانية تضم (94) غير رياضي. تم تقدير النمط الجسمي باستخدام الطريقة الأنتروبومترية أشارت نتائج الدراسة إلى وجود فروق معنوية بين الرياضيين وغير الرياضيين في مكونات النمط الجسمي، حيث كانت لصالح الرياضيين في مكوني العضلية والنحافة، في حين جاءت لصالح غير الرياضيين في مكون السمانة، والجدير بالملاحظة ان التغيرات المعنوية التي طرأت على مكونات النمط الجسمي لم تؤدي الى تحول جذري في النمط الجسمي لعينة الدراسة، حيث نجد ان النمط عضلي نحيف (-342-) هو السائد لدى مجموعة الرياضيين، بينما لدى غير الرياضيين النمط السمين المتوازن(2-24-) هو الغالب وهذا طيلة الأربع سنوات التي استغرقتها الدراسة. Abstract: This study aimed to determine the somatotype of a population of young athletes participating in a sports-study program. Have them compared to their non-athletic colleagues The sample is made up of 188 boys aged 12 to 15 divided into two groups: athletic (n = 94) and non-athletic (n = 94). We determined their somatotype according to the method of Heath and Carter. The results of this study revealed significant differences between the two groups in somatotype components, in favor of athletes for the mesomorphic and ectomorphic components, but in favor of non-athletes for the endomorphic component. On the other hand, we observed a stability of the somatotype from 12 to 15 years of mesomorphic-ectomorphic type (2-4-3) for the group of athletes and of endomorphic-balanced type (4-2-2) for the group of non athletes, despite the significant evolution of the three components of the somatotype.
مقال
Keywords: النمط الجسمي ؛ الرياضيين ؛ غير رياضيين ؛ الناشئين; Somatotype ; Athletes; Non-athletes